Biogenic Synthesis, Characterization of Cerium Oxide Nano Particles using Perioria pinnatum Leaf Extract and Its Applications - Madhu, R.; Pruthviraj , K.; Sreenivasa , S.; Suresh , D.; Swamy, B. E. K.; Prakash , M. S. (Journal of Scientific Research, 2023)
The biogenic method of synthesis of metal oxide nanoparticles is the recent advances development in nanotechnology, and cerium oxide (CeO2) nanoparticles (NPs), in particular, are advantageous due to their remarkable properties. In this report, we discuss the results of Cerium oxide NPs synthesized by solution-combustion method using “Perioria pinnatum” leaf extract as a reducing and stabilizing agent. The structurally spherical shaped CeO2 NPs with 12 nm crystal size were synthesized and further characterized by powder X-ray diffraction analysis (PXRD), Fourier transforms infrared spectroscopy (FT-IR), and Scanning electron microscopy (SEM) and with Energy dispersive X-ray (EDX) analysis. XRD pattern confirmed the formation of CeO2 NPs with FCC structure. Further, green synthesized CeO2 nanoparticles were assessed for their in-vitro antioxidant activity, visible light-induced dye degradation property against methylene blue, and in electrical cells modified with CeO2 NPs that could electrochemically sense Dopamine (DA) up to 11 µM.